The Influence of Leadership Style on Employee Performance Mediated by Job Satisfaction and Moderated by Work Motivation - Soetirto, Muhammad Mirza; Muldjono, Pudji; Hidayatulloh, Furqon Syarief (Ridwan Institute, 2023)
This study aims to examine the effect of work motivation on performance mediated by. The approach used in this research is a quantitative approach. The sample used in this study were employees of PT TTNT, totaling 77 respondents. The research data was obtained from the results of filling out the questionnaire and analyzed using the PLS SEM analysis technique with the help of the SmartPLS program. The results of this study indicate that (1) leadership style has a positive and significant effect on employee job satisfaction. The better the superior's leadership style, the higher the employee's job satisfaction, and vice versa the worse the leadership, the lower the employee's job satisfaction; (2) leadership style influences employee performance, the results of this study indicate that a good leadership style does not always produce high employee performance. The results of this study indicate that leadership style can improve employee performance if the leadership style can shape employee job satisfaction; (3) The results of this study succeeded in proving that job satisfaction affects performance. The higher the employee's job satisfaction, the higher the employee's performance, conversely, low employee satisfaction will reduce employee performance; (4) Job satisfaction can mediate the effect of leadership style on job satisfaction. A good leadership style can increase employee job satisfaction which will further improve employee performance; (5) Work motivation has a positive effect on performance.